(untitled) (REVISTA SAYWA, 2020)
Particle physics has always been a subject of interest not only for scientists but also for the general public. The mankind has always questioned about the nature of the Universe and matter composition. In this article we will briefly describe the Standard Model of particles, theory that explains the properties and interactions between the elementary particles, and how we measure them experimentally. In particular, we will focus on the description of the LHC and one of its detectors ATLAS, and its Collaboration with Universidad Antonio Nariño’s Experimental High Energy group